(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the corrupt factors are manifested in the unhealthy environment created by the society in which this phenomenon lives. In turn, legal literacy not only improves the environment of the society, but also strengthens civil control and democratic institutions, increases the participation of the population in legal creativity, and leads to the growth of the economy. The article reveals the essence of social values ​​- the main factor in the spread of corruption, its ways and methods.